The Effect of Loading and Unloading Costs, Vessel Arrival Punctuality and Container Availability on Re-Use Intention - Cantika Putri Agustina; Muhammad Tohir (Siber Journal of Transportation and Logistics, 2025)
The effect of  Loading and unloading Costs, Vessel Arrival Punctuality, and Container Availability on Re-use Intention  is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Loading and unloading Costs has an effect on Re-use Intention; 2) Vessel Arrival Punctuality has an effect on Re-use Intention; and 3) Container Availability has an effect on Re-use Intention.